Formação, competências e atuação em Biblioteconomia para área de Ciências da Saúde: uma análise sob o olhar dos profissionais da região sudeste do Brasil - Débora Crystina Reis (2022)
Librarians can work in different areas, given the interdisciplinary characteristic of the Librarianship and Information Science area and its objectives to assist in the organization, treatment, registration, retrieval, and dissemination of information in any support and way. In the area of Health Sciences, librarians must have and acquire certain skills and abilities to meet the characteristic demands of this field. This need was presented in the 1940s in the United States, at first with medical libraries. From this context, the question of this research appears, asking whether the knowledge acquired during graduation supports the performance in the health area, that is, what is the impact of undergraduate education in the performance in the health area for librarians? To answer this question, the research presented in this dissertation is justified. As for its objectives, the general objective is: to identify, from the perspective of librarians who work in the health area, what are the impacts on their performance, caused by the gaps in the little approach to health information in their training, in the states of Southeast region. As specific objectives: a) to map and identify the professionals and the main informational environments of action in Health Sciences in the Southeast region of Brazil; b) to identify the professional skills identified by librarians working in the area; c) to identify, from the librarians' reports, the innovations in services performed by them in the pandemic; and d) to propose, from the professionals' speeches, themes to be worked on in training in Library Science. As for its methodology, the research can be considered applied and characterized as quali- quantitative. From its objectives it can be classified as descriptive research, which adopts the survey as methodological procedures. As technical procedures, the research is bibliographic, with data collection via electronic form. As results, it was identified that librarians feel less fit or unfit in various activities. In addition, they reaffirmed the generalist character of the librarian training. Then, a profile of the librarians in health who answered the questionnaire was outlined, most of them white women, between 30 and 39 years old, who work in public or private universities. Regarding the skills needed to act, the respondents emphasized mainly knowledge in controlled vocabularies, research in databases and methodology. In relation to the performance in the pandemic, several innovations made by librarians were identified, such as newsletters, repositories, and greater digital performance with users. However, there is a need for more research on health information in library education.